BLIMP-1-dependent differentiation of T follicular helper cells into Foxp3+ T regulatory type 1 cells - Garnica, Josep; Yamanouchi, Jun; Clarke, Robert; Moro, Joel; Thiessen, Shari; Montaño, Javier; Mondal, Debajyoti; Serra, Pau; Santamaria, Pere (Frontiers in Immunology, 2025)
T-regulatory-type-1 (TR1) cells are a subset of interleukin-10-producing but Foxp3– Treg cells that arise in response to chronic antigenic stimulation. We have shown that systemic delivery of autoimmune disease-relevant peptide-major histocompatibility complex class II (pMHCII)-coated nanoparticles (pMHCII-NP) triggers the formation of large pools of disease-suppressing Foxp3– TR1 cells from cognate T-follicular helper (TFH) cell precursors. Here we show that, upon treatment withdrawal, these Foxp3– TR1 cells spontaneously differentiate into a novel immunoregulatory Foxp3+ TR1 subset that inherits epigenetic and transcriptional hallmarks of their precursors, including clonotypic T-cell receptors, and is distinct from other Foxp3+ Treg subsets. Whereas the transcription factor BLIMP-1 is dispensable for development of conventional Foxp3+ Treg cells, it is necessary for development of Foxp3+ TR1 cells. In a model of central nervous system autoimmunity, abrogation of BLIMP-1 or IL-10 expression in the Foxp3– and/or Foxp3+ TR1 subsets inhibits their development or anti-encephalitogenic activity. Thus, the TFH-TR1 transdifferentiation pathway results in the generation of two distinct autoimmune disease-suppressing, IL-10-producing TR1 subsets that are distinguished by the expression of Foxp3 and Foxp3 target genes.